1998
DOI: 10.1002/(sici)1097-4644(19980801)70:2<193::aid-jcb5>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

The nucleus: A target site for parathyroid hormone-related peptide (PTHrP) action

Abstract: It is becoming increasingly apparent that parathyroid hormone-related peptide (PTHrP) modulates cellular function in a dual mode of action: first, by binding and activating its cognate cell surface G-protein-coupled receptor and, second, by direct intracellular effects following translocation to the nucleus and/or nucleolus of the target cell. Little is presently known about the mechanisms and events that determine the timing and degree of PTHrP nuclear translocation or the role it may serve in normal or dysre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
37
0
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 37 publications
1
37
0
1
Order By: Relevance
“…In this model, PTHrP secretion results from trafficking of the precursor to the endoplasmic reticulum directed by a typical signal peptide. [3][4][5][6] In addition to this typical neuroendocrine trafficking and secretion, PTHrP is unusual in that it is also able to traffic to the nucleus of multiple cells [7][8][9][10][11][12][13][14] (Figure 1). This "bidirectional trafficking" results from the presence in the PTHrP sequence of alternate translational initiation sites, 1 of which uses an AUG translational initiation codon directly upstream of the signal peptide, as well as a second functional CUG translational initiation codon, which is internal to, and therefore disrupts, the signal peptide.…”
mentioning
confidence: 99%
“…In this model, PTHrP secretion results from trafficking of the precursor to the endoplasmic reticulum directed by a typical signal peptide. [3][4][5][6] In addition to this typical neuroendocrine trafficking and secretion, PTHrP is unusual in that it is also able to traffic to the nucleus of multiple cells [7][8][9][10][11][12][13][14] (Figure 1). This "bidirectional trafficking" results from the presence in the PTHrP sequence of alternate translational initiation sites, 1 of which uses an AUG translational initiation codon directly upstream of the signal peptide, as well as a second functional CUG translational initiation codon, which is internal to, and therefore disrupts, the signal peptide.…”
mentioning
confidence: 99%
“…PTHrP may modulate cellular function in a dual mode of action: ®rst, by binding and activating its cognate cell surface Gprotein-coupled receptor and, second, by direct intracellular eects following translocation to the nucleus and/or nucleolus of the target cell. 5 PTHrP can be secreted by either the regulated secretory pathway, or the constitutive secretory pathway. The cellular response to PTHrP-nuclear interaction is cell- PTHrP has been implicated as an autocrine modulator of growth and dierentiation in the colon.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent research has identified several normal physiological actions including growth and development, calcium homeostasis and smooth muscle relaxation (Wysolmerski and Broadus, 1994). Parathyroid hormone-related protein acts locally in an autocrine, paracrine or intracrine manner (Broadus et al, 1985;Burtis et al, 1987;Suva et al, 1987) with intracrine activity being the result of translocation to the nucleus, mediated by a bipartite nuclear localisation sequence (NLS) within the mid-region of the PTHrP peptide (Nguyen and Karaplis, 1998). Nuclear-localised PTHrP has been shown to be both mitogenic and antiapoptotic (Aarts et al, 2001;.…”
mentioning
confidence: 99%